Essential oils: pharmaceutical applications and encapsulation strategies into lipid-based delivery systems - Cimino, Cinzia (2021)
Essential oils are being studied for more than 60 years, but a growing interest has emerged in the recent decades due to a desire for a rediscovery of natural remedies. Essential oils are known for millennia and, already in prehistoric times, they were used for medicinal and ritual purposes due to their therapeutic properties. Using a variety of methods refined over the centuries, essential oils are extracted from plant raw materials: the choice of the extraction method is decisive, since it determines the type, quantity, and stereochemical structure of the essential oil molecules. To these components belong all properties that make essential oils so interesting for pharmaceutical uses; the most investigated ones are antioxidant, anti-inflammatory, antimicrobial, wound-healing, and anxiolytic activities. However, the main limitations to their use are their hydrophobicity, instability, high volatility, and risk of toxicity. A successful strategy to overcome these limitations is the encapsulation within delivery systems, which enable the increase of essential oils bioavailability and improve their chemical stability, while reducing their volatility and toxicity. Among all the suitable platforms, our review focused on the lipid-based ones, in particular micro- and nanoemulsions, liposomes, solid lipid nanoparticles, and nanostructured lipid carriers.